Depersonalization/derealization and its relationship with psychological flexibility in students at a Brazilian federal university - Araujo, Lucas Augusto Luvison de; Salgado, Ana Carolina Sarquis; Neves, Luísa Müller; Terra, Mauro Barbosa (Perspectivas em Análise do Comportamento, 2025)
Depersonalization/Derealization (DP/DR) is a psychological experience characterized by a sense of strangeness, disconnection, and unreality towards oneself and the surrounding world. These symptoms seem to be related to greater difficulty in experiencing psychological events, and possibly with less psychic flexibility. Acceptance and Commitment Therapy (ACT) emphasizes the importance of psychological flexibility for mental health. Therefore, the present study aimed to investigate the relationship between psychological flexibility and DP/DR symptoms in students. A cross-sectional study was conducted where online data were collected from 94 students, mostly female and studying nursing. A moderate negative correlation was found between total scores of psychological flexibility and DP/DR, as well as specific subscales related to openness to experience and depersonalization. These findings indicate that individuals with more DP/DR symptoms tend to have lower psychological flexibility. These findings suggest that addressing psychological flexibility, especially in the processes of acceptance and defusion, may be helpful in treating this population, which requires further investigation.